Selected and extended papers of the Brazilian Symposium on Programming Languages 2012 - Junior, Francisco Heron Carvalho (2014)
The Brazilian Symposium on Programming Languages (SBLP) is an annual conference romoted by the Brazilian Computer Society (SBC), which has become an important forum for researchers and practitioners in programming language design and implementation from around the world to interact and present their results and experience. This issue of Science of Computer Programming includes extended versions of selected papers from the XVI SBLP, held in Natal, Brazil on September 23–28, 2012.